Immuno-oncological drugs application in the treatment of metastatic cutaneous melanoma with lymph nodes metastases of rare localization: a case report - A. P. Polyakov; L. V. Bolotina; A. L. Kornietskaya; D. S. Kudashkina; D. V. Sidorov; A. A. Troitskiy; A. R. Gevorkov (Опухоли головы и шеи)
Cutaneous melanoma is characterized by an aggressive course associated with a tendency to metastasis. For a long time, the prognosis of patients with metastatic melanoma remained extremely poor. However, the introduction of immunooncological drugs into clinical practice has changed the approaches to the treatment of patients with metastatic melanoma, and fundamentally improved the prognosis and quality of life of such patients, which undoubtedly became a breakthrough in the treatment of this pathology. This article presents a clinical case of the treatment with immunological drugs of a patient with metastatic melanoma of the skin with lymph nodes of rare localization with a complete tumor response.